2021
DOI: 10.1080/19942060.2021.1913232
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic axial plunger pump: gaseous and vaporous cavitation characteristics and optimization method

Abstract: Gaseous and vaporous cavitation have extremely harmful effects on hydraulic axial plunger pumps, reducing flowrate and increasing flow pulsation. The collapse of vapor bubbles strongly impacts the inner wall and produces many pits. Therefore, it is very important to reduce gaseous and vaporous cavitation to improve the performance of hydraulic axial plunger pumps. In this work, a full cavitation model and a compressible model are used to simulate the two kinds of cavitation, which are validated by a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…At present, plunger grouting pumps are mainly used in grouting projects, and their basic motion is driven by crankshaft rotation to complete the reciprocating motion of the plunger in the cylinder. However, the reciprocating motion of the plunger results in a moment of inertia and imbalance of the inertial force, which causes an increase in the inertial load on the support members of the plunger pump structure [6][7][8][9]. The plunger produces different degrees of cyclic pressure per stroke, and the grouting pressure and flow are difficult to control, with pressure fluctuations ranging from a few to more than a dozen megapascals.…”
Section: Introductionmentioning
confidence: 99%
“…At present, plunger grouting pumps are mainly used in grouting projects, and their basic motion is driven by crankshaft rotation to complete the reciprocating motion of the plunger in the cylinder. However, the reciprocating motion of the plunger results in a moment of inertia and imbalance of the inertial force, which causes an increase in the inertial load on the support members of the plunger pump structure [6][7][8][9]. The plunger produces different degrees of cyclic pressure per stroke, and the grouting pressure and flow are difficult to control, with pressure fluctuations ranging from a few to more than a dozen megapascals.…”
Section: Introductionmentioning
confidence: 99%
“…While the vapour cavitation is accompanied by the phase change between liquid and gas phases, gas cavitation is associated with diffusion processes in the liquid [2,11]. Liquids are affected by both processes [6][7][8][9], and both significantly affect the hydraulic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Suo et al proposed a full cavitation model and compressibility model to simulate the influence of cavitation on the flow rate of the piston pump. 19 Gullapalli et al used an experiment to study the influence of oil gas content on flow loss and noise of the piston pump, the results showed that the volume efficiency of the piston pump decreased, the mechanical efficiency increased slightly, and the overall efficiency decreased with the increase of gas content. 20 Vacca et al analyzed the influence of cavitation on the effective flow rate of swash-plate piston pumps based on compressible flow models.…”
Section: Introductionmentioning
confidence: 99%